Interleukin-10 of Positive and Negative HIV RNA Patients in Dr. Moewardi General Hospital in Surakarta - Pradeta, Emirita Wulan; Prasetyo, Afiono Agung; Sari, Yulia (Nexus Biomedika, 2015)
Background: HIV infection may cause imbalance of immune system and impacts on IL-10 status which has several immunological roles that may affect HIV infection itself. The aim of this study was to investigate the association between IL-10 and HIV RNA status. Methods: The IL-10 levels in the plasma samples obtained from 60 HIV patients in Dr. Moewardi General Hospital in Surakarta were analyzed by ELISA (Enzyme-Linked Immunosorbent Assay). Results: Elevated IL-10 level was found in 21.7% (13/60) samples and predominantly in positive HIV RNA (OR 2.67; 95% CI 0.40-17.96) and male (OR 1.22; 95% CI 0.36-4.17) patients. Conclusion: Elevated IL-10 level was associated with positive HIV RNA status and gender. Keywords: IL-10, HIV RNA